Innovation and humanization in child care: professionals from Ceará who make the difference - Arruda, Lucas Giannini de Oliveira Conrado; Santana, Marília Freitas; Barbosa , Gabriele Sousa; de Lima , Amanda Medeiros; Veras , Igor Moreira; de Souza , Liane Carvalho de Brito; Maia, Flávio Lobo; de Castro, Rodrigo José Alencar; Collares , Danielle Moreira; Gomes , Josenília Maria Alves (Brazilian Journal of Case Reports, 2021)
Within a regional context, these experience reports cited the practice of some health professionals, they did a wonderful work in theirs pediatric centeres which are reference in pediatric care. In this context of affection and humanity, we highlight examples of people who word with love in the art of caring. And this article shares theirs improvements, indeed, we hope these achievements enlighten other people.